1998
DOI: 10.1046/j.1537-2995.1998.38598297213.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in endogenous thrombopoietin in healthy donors after automated plateletpheresis

Abstract: Single-donor plateletpheresis results in a temporary increase in serum TPO levels in healthy platelet donors, which may be part of a compensatory response-boosting megakaryocytopoiesis after platelet collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 20 publications
4
29
1
Order By: Relevance
“…37 Indeed, prior studies have shown that serum thrombopoietin levels are increased after plateletpheresis procedures for platelet donation. 38,39 In turn, increased thrombopoietin levels might lead to enhanced CD34 ϩ responses because of expansion of the marrow progenitor pool. 40 It is also possible that the relative lymphopenia produced after lymphapheresis might have resulted in a positive effect on mobilization through a process similar to homeostatic recycling and peripheral expansion, which has been reported to occur for T cells in lymphopenic states.…”
Section: Discussionmentioning
confidence: 99%
“…37 Indeed, prior studies have shown that serum thrombopoietin levels are increased after plateletpheresis procedures for platelet donation. 38,39 In turn, increased thrombopoietin levels might lead to enhanced CD34 ϩ responses because of expansion of the marrow progenitor pool. 40 It is also possible that the relative lymphopenia produced after lymphapheresis might have resulted in a positive effect on mobilization through a process similar to homeostatic recycling and peripheral expansion, which has been reported to occur for T cells in lymphopenic states.…”
Section: Discussionmentioning
confidence: 99%
“…Among females, this decrease tends to be greater [32,33]. Interestingly, the fall in platelet count does not correlate with the yield of the plateletpheresis procedure as more platelets are collected than anticipated due to the mobilization of platelets from the spleen during collection [29].…”
Section: Bleeding Thrombocytopeniamentioning
confidence: 93%
“…Interestingly, the fall in platelet count does not correlate with the yield of the plateletpheresis procedure as more platelets are collected than anticipated due to the mobilization of platelets from the spleen during collection [29]. Dettke et al found the time required for a donor to return to baseline following a platelet donation to be four days in males with a delay in increase of thrombopoietin levels and a corresponding delay in return to normal platelet counts in females [33]. In donors undergoing alternate day collections, platelet count and apheresis yields have been shown to return to baseline levels by day 10 of collection with stabile counts and yields with subsequent collections [34].…”
Section: Bleeding Thrombocytopeniamentioning
confidence: 99%
“…This finding might be the result of increased serum levels of hematopoietic growth factors, which were stimulated by the number of cells removed during the leukapheresis procedure. Several publications have reported that serum levels of thrombopoietin (TPO) were significantly increased up to 7 days after plateletpheresis [19,20,21]. Furthermore, Dettke et al [19] detected a decline in serum TPO levels as PLT counts increased.…”
Section: Discussionmentioning
confidence: 99%
“…Several publications have reported that serum levels of thrombopoietin (TPO) were significantly increased up to 7 days after plateletpheresis [19,20,21]. Furthermore, Dettke et al [19] detected a decline in serum TPO levels as PLT counts increased. Weisbach et al [21], who focused on systemic levels of diverse hematopoietic growth factors, found likewise a significantly increased erythropoietin level after plateletpheresis, whereas the stem cell factor levels decreased significantly.…”
Section: Discussionmentioning
confidence: 99%